2013 Ieee Ro-Man 2013
DOI: 10.1109/roman.2013.6628409
|View full text |Cite
|
Sign up to set email alerts
|

Comfortable approach distance with small Unmanned Aerial Vehicles

Abstract: Abstract-This paper presents the first known humansubject study of comfortable approach distance and height for human interaction with a small unmanned aerial vehicle (sUAV), finding no conclusive difference in comfort with a sUAV approaching a human at above head height or below head height. Understanding the amount, if any, of discomfort introduced by a sUAV flying in close proximity to a human is critical for law enforcement, crowd control, entertainment, or flying personal assistants. Previous work has foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…[16] examined the maneuver position of a drone that minimizes danger or stress when a drone interacts with people in public places. It was found that drones that interact with people are considered social robots (beings) and, hence, are required to remain at an appropriate distance or position, similar to humans interacting with humans in daily life.…”
Section: Researchmentioning
confidence: 99%
“…[16] examined the maneuver position of a drone that minimizes danger or stress when a drone interacts with people in public places. It was found that drones that interact with people are considered social robots (beings) and, hence, are required to remain at an appropriate distance or position, similar to humans interacting with humans in daily life.…”
Section: Researchmentioning
confidence: 99%
“…Bethel and Murphy defined several zones for robot interaction: the intimate zone (0-0.46 m), the personal zone (0.46-1.22 m, maximum distance for communication), the social zone (1.22-3.66 m) and the public zone (further than 3.66 m) (Bethel and Murphy 2008;Murphy 2004). More recent work has extended this to UAVs (Duncan and Murphy 2013).…”
Section: Related Work On Trust and Robotsmentioning
confidence: 99%
“…Recent research has begun to examine perceptions of aerial robot morphology [2] and proxemics [8]. Additionally, research has explored the implicit expression of flight intent [34] and affect [33] by manipulating aerial trajectories, velocities, and accelerations across three spatial dimensions.…”
Section: Introductionmentioning
confidence: 99%